Liderança na pandemia de Covid-19: um estudo sobre o estilo de liderança adotado e os desafios enfrentados no ambiente virtual - Lima, Amanda de Oliveira (Universidade Federal de São Carlos, 2022)
The Covid-19 pandemic has brought with it countless changes in different spheres of everyday life, including the business world. Because of it, thousands of employees have started working remotely, in the model known as home office. The purpose of this article is to study how the quick transition to the virtual environment has affected leadership, in terms of style and challenges faced. Thereunto, a survey questionnaire was developed and applied to members of virtual teams in order to understand what has been perceived about the leadership style by them. In addition, interviews were also carried out with leaders to capture the challenges experienced during this period. Thereafter, both questionnaire and interviews had their questions individually analyzed. This process revealed the predominance of the Transformational style of leadership as well as the fact that proximity to the team, psychological issues and family settings are among the main challenges of the period for leaders.
Leadership in the Covid-19 pandemic: a study about the leadership style adopted and the challenges faced in the virtual environment
Keywords: Liderança; Times Virtuais; Covid-19; Leadership; Virtual Times; Pandemic; Remote Work; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DE RECURSOS HUMANOS